2016
DOI: 10.1371/journal.pone.0168423
|View full text |Cite
|
Sign up to set email alerts
|

3’UTR Polymorphism in ACSL1 Gene Correlates with Expression Levels and Poor Clinical Outcome in Colon Cancer Patients

Abstract: Strong evidence suggests that lipid metabolism (LM) has an essential role in tumor growth to support special energetic and structural requirements of tumor cells. Recently, overexpression of LM-related genes, apolipoproteins related to metabolic syndrome, and ACSL/SCD network involved in fatty acid activation have been proposed as prognostic markers of colon cancer (CC). Furthermore, activation of this latter lipid network has been recently demonstrated to confer invasive and stem cell properties to tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…A recent bioinformatics study (37) utilizing online databases Oncomine (https://www.oncomine.org/resource/login .html) and PrognoScan (http://www.abren.net/PrognoScan/) stated certain novel associations between ACSL expression and cancer survival outcomes. On the one hand, which was in line with previous findings (12,18,27), the study showed that the overexpression of either ACSL1 or ACSL4 was associated with a poorer prognosis in patients with colon cancer, and that ACSL5 downregulation was associated with poor survival in breast cancer patients. On the other hand, the study suggested certain novel links.…”
Section: Deregulated Expression Of Acsls In Clinical Cancersupporting
confidence: 91%
See 2 more Smart Citations
“…A recent bioinformatics study (37) utilizing online databases Oncomine (https://www.oncomine.org/resource/login .html) and PrognoScan (http://www.abren.net/PrognoScan/) stated certain novel associations between ACSL expression and cancer survival outcomes. On the one hand, which was in line with previous findings (12,18,27), the study showed that the overexpression of either ACSL1 or ACSL4 was associated with a poorer prognosis in patients with colon cancer, and that ACSL5 downregulation was associated with poor survival in breast cancer patients. On the other hand, the study suggested certain novel links.…”
Section: Deregulated Expression Of Acsls In Clinical Cancersupporting
confidence: 91%
“…Upregulation of ACSL1 was found in multiple types of cancer, including colon (11,12), breast (13) and liver (14,15) cancer, and myeloma (16), while downregulation was found in lung squamous cell carcinoma (17). More importantly, ACSL1 overexpression was associated with a poor clinical outcome in colon cancer patients (18). Like those of ACSL1, the majority of studies of ACLS4 favor an oncogenic role.…”
Section: Deregulated Expression Of Acsls In Clinical Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…20 Acyl-CoA synthetase long-chain family member 1 (ACSL1) is one of the distinct members of ACSLs family and has been regarded as an oncogene in some cancers. 10,11,21 In this study, ACSL1 was overexpressed in TC cells. When SNHG7 was downregulated, the expression of ACSL1 was inhibited.…”
Section: Discussionmentioning
confidence: 78%
“…Regarding CRC, key enzymes involved in lipid-metabolic pathways have been found differentially expressed in normal and tumoral tissues. Some of them were associated with cancer survival and were individually proposed as prognosis markers [ 6 , 10 , 11 ]. Furthermore, one of the transcriptomic consensus molecular subtypes (CMS) of CRC described by Guinney and colleagues [ 12 ], the “metabolic subtype 3” (CMS3), exhibits a clear enrichment for multiple metabolism signatures along with KRAS (Kirsten Rat Sarcoma Viral Oncogene Homolog)-activating mutations that have been described as inducing metabolic reprogramming [ 12 ].…”
Section: Introductionmentioning
confidence: 99%